Late Onset Horner's Syndrome during Postoperative Epidural Analgesia - Rani, Kanchan; Prasad, Mukesh Kumar (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v5i1.5066 NJOG 2010 Jul-Aug; 5(1): 60